2012
DOI: 10.1155/2012/260909
|View full text |Cite
|
Sign up to set email alerts
|

tRNA-Derived Fragments Target the Ribosome and Function as Regulatory Non-Coding RNA inHaloferax volcanii

Abstract: Nonprotein coding RNA (ncRNA) molecules have been recognized recently as major contributors to regulatory networks in controlling gene expression in a highly efficient manner. These RNAs either originate from their individual transcription units or are processing products from longer precursor RNAs. For example, tRNA-derived fragments (tRFs) have been identified in all domains of life and represent a growing, yet functionally poorly understood, class of ncRNA candidates. Here we present evidence that tRFs from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
244
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 236 publications
(262 citation statements)
references
References 35 publications
8
244
2
3
Order By: Relevance
“…57 These differences in tRNA specificities, abundance, and length support the conclusion that distinct biogenesis mechanisms are at work.…”
Section: Trna-derived Fragmentsmentioning
confidence: 83%
See 2 more Smart Citations
“…57 These differences in tRNA specificities, abundance, and length support the conclusion that distinct biogenesis mechanisms are at work.…”
Section: Trna-derived Fragmentsmentioning
confidence: 83%
“…18 A markedly different cellular function for 5′ tRFs has been very recently proposed. 57 In the archaeon Haloferax volcanii, a 26 nt-long tRF originating from tRNA…”
Section: Trna-derived Fragmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same study also reported that the 5Ј-terminal oligoguanine sequence is essential for the translational repression ability of these tiRNAs (23). The translation inhibitory effect of tRNA fragments has been also reported in other organisms; the 26-nucleotide 5Ј-tRFs derived from tRNA Val have been shown to inhibit translation in the archaeon Haloferax volcanii (24). Similar to tiRNAs, Val-tRF is produced in a stress-dependent manner.…”
Section: Role Of Tirnas In the Cellular Stress Response And Other Patmentioning
confidence: 59%
“…First, they are not restricted to one domain of life since they have been found in archaea, bacteria as well as in uni-and multicellular eukarya. Second, the biological roles of tdRs embrace regulation of transcription (6), translation (5,(7)(8)(9), stress granule formation (10), apoptosis (11), cell proliferation (12,13), RNAi (14), vesicle-mediated intercellular communication (6), and intergenerational inheritance (15) (Figure 1). Therefore, the mere detection of a tRNA fragment in a deep-sequencing screen does not allow reasonable deductions to be made about its biogenesis or function.…”
mentioning
confidence: 99%